Determinants of Food Insecurity in Pakistan: An Empirical Investigation at Household Level - Ullah, Sami; Abro, Asif Ali; Mustafa, Ahmed Raza ul; Ali, Muhammad Sibt e (Pakistan Journal of Humanities and Social Sciences, 2023)
Pakistan is facing severe level of food insecurity in terms of physical and economic access. In this regard, current study will focus to empirically investigate the leading determinants of food insecurity by using HIES 2019 data set. Household Expenditures Survey (HES) method will be used to find the status of food insecurity in Pakistan. In this method, the information about the quantities and expenditure of food is used to find the incidence of food insecurity at household level. Further, logistic regression model was the most appropriate technique for analyzing the determinants of food insecurity in Pakistan. This study concluded that there is negative and significant relationship between size of household, distance of drinking water and food insecurity status at household level. Whereas, the positive relationship is found between food insecurity status and income level of the households, expenditure of the household, level of family head education, age of the head and male head of the household. Study suggests that, policies should be adopted to increase income level of the household, education level (to raise literacy rate), social welfare, and employment opportunities etc. Policy makers should design policies to increase physical, social and economic access toward healthy food by prioritizing agriculture sector as the life line for sustainable development and inclusive growth in the long run.